2006
DOI: 10.1200/jco.2005.05.2084
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Phosphorylase Expression Is Associated With Response to Capecitabine Plus Irinotecan in Patients With Metastatic Colorectal Cancer

Abstract: These data indicate that capecitabine plus irinotecan is an active regimen against mCRC. The biomarker analysis (including metastatic tissue) was feasible in a multicenter setting, and provides preliminary evidence that TP expression may be a predictive marker for response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 31 publications
2
59
2
Order By: Relevance
“…10,11,18,24 The current study further supports the importance of TP gene expression as a potential prognostic marker in this disease by demonstrating a significant association with an increased probability of response to a 5-FU-based regimen, and better TTP and OS in patients with low TP expression. However, Meropol et al 28 showed recently using IHC that any level of staining for TP in patient samples with metastatic CRC was associated with better response rates to a CAPIRI regimen. The ability of TP to predict patient outcomes to such regimens, however, has yet to be confirmed in larger prospective trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,18,24 The current study further supports the importance of TP gene expression as a potential prognostic marker in this disease by demonstrating a significant association with an increased probability of response to a 5-FU-based regimen, and better TTP and OS in patients with low TP expression. However, Meropol et al 28 showed recently using IHC that any level of staining for TP in patient samples with metastatic CRC was associated with better response rates to a CAPIRI regimen. The ability of TP to predict patient outcomes to such regimens, however, has yet to be confirmed in larger prospective trials.…”
Section: Discussionmentioning
confidence: 99%
“…11,32 One reason may be the use of RT-PCR vs. IHC. In the CAPIRI study, 28 when the authors attempted to validate the IHC results against the RT-PCR analysis on the same tissues, the IHC findings on TP predictive value were less consistent. Sample size was an issue in this study; however, the authors underscored the need for confirmatory prospective trials to validate TP as a biomarker in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Other predictive parameters of capecitabine toxicity include the aforementioned mutations of MTHFR 1298 A-C and 677C-T, as reported in a recent study by Sharma et al 66 MTHF 677C-T mutation was associated with a better response to capecitabine treatment. Meropol et al 67 studied the correlation of TP expression in advanced CRC patients treated with capecitabine and irinotecan, and reported a positive association between high expression of TP in primary tumors and response to chemotherapy. A study from Japan on CRC patients treated with adjuvant 5 0 -deoxy-5-fluorouridine (5 0 -DFUR, doxifluridine), a capecitabine metabolite, showed that high TP levels, low DPD levels and a higher TP/DPD ratio were all associated with better disease-free and overall survival.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%
“…With the combination of capecitabine and irinotecan, patients whose tumor had TP expression by immunohistochemistry had improved overall survival, whereas TS and DPD were not predictive. 69 High expression of ERCC1 and TS mRNA in patients with advanced colorectal cancer treated with 5-FU and oxaliplatin has been associated with poorer survival. 70 In rectal cancer patients treated with chemoradiation with a 5-FU regimen, high intratumoral TS after therapy was reported to be predictive of unfavorable outcome.…”
Section: Markers In Combination Therapy Regimensmentioning
confidence: 99%